2015
DOI: 10.15282/ijame.12.2015.1.0236
|View full text |Cite
|
Sign up to set email alerts
|

Direct injection of water mist in an intake manifold spark ignition engine

Abstract: The purpose of this study is to investigate the effects of water mist (WM) injected directly into an intake manifold spark ignition (SI) engine. WM flows through a nozzle at the throttle body of the four-cylinder four-stroke multi-point injection engine for testing the performance of exhaust emission system. The water is pumped in mist form into the intake manifold with an air-fuel mixture through the nozzle, which is located on the throttle body. Experimental work and simulation methods are combined by the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Augmented regulations on particulate matter and NOx, and also issues raised on greenhouse gas emission like CO2 are the reasons for demanding research work on bio-fuels all over the world [3][4][5][6]. Biodiesel derived from the trans-esterification of fats and oils [7][8][9][10][11] is a possible fuel for diesel engines. The properties of this fuel is comparable to that of diesel and can be used directly to run existing diesel engines or as a blend with crude oil diesel [12].…”
Section: Introductionmentioning
confidence: 99%
“…Augmented regulations on particulate matter and NOx, and also issues raised on greenhouse gas emission like CO2 are the reasons for demanding research work on bio-fuels all over the world [3][4][5][6]. Biodiesel derived from the trans-esterification of fats and oils [7][8][9][10][11] is a possible fuel for diesel engines. The properties of this fuel is comparable to that of diesel and can be used directly to run existing diesel engines or as a blend with crude oil diesel [12].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the increase in CO is observed at maximum load condition. This is due to decrease in combustion temperature which leads to partial oxidation of CO to CO2 conversion process [27,29]. It is observed that when the load increased from 10% to 75 % the CO emissions are decreased for 3% DEE and 6% DEE blends respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The HCCI technique is the process by which a homogeneous mixture of air and fuel is compressed until auto-ignition occurs near the end of the compression stroke, followed by a combustion process that is significantly faster than either compression ignition (CI) or spark ignition (SI) combustion [11][12][13][14]. The air/fuel mixture quality in HCCI engines is generally lean, auto-ignites in multiple locations and is then burned volumetrically without discernible flame propagation [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%